A systematic review of current studies in patients with familial hypercholesterolemia by use of national familial hypercholesterolemia registries. Issue 4 (August 2016) - Mundal, Liv; Retterst⊘l, Kjetil
Abstract : Purpose of review: More than 25 million are expected to have familial hypercholesterolemia worldwide. The risk of cardiovascular disease (CVD) in familial hypercholesterolemia is not clear and register studies represent a valuable tool to get such data, which will be discussed in the present paper. Recent finding: A systematic review of current familial hypercholesterolemia studies, by use of National familial hypercholesterolemia registries was performed from 1980 to 2016. This review shows that familial hypercholesterolemia patients have a high prevalence of CVD also in the time period after statins became available. The patient group does not reach recommended target values for lipids, and have a significantly higher CVD mortality as compared with the general population according to age and sex. Summary: The review underscores the importance of establishing National familial hypercholesterolemia registries with complete datasets on familial hypercholesterolemia patients to improve early diagnostics, therapeutics and long-term follow-up to prevent the premature CVD events and deaths in this patient group.